2011
DOI: 10.1111/j.1600-051x.2011.01825.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping biological to clinical phenotypes during the development (21 days) and resolution (21 days) of experimental gingivitis

Abstract: Levels of substance P, cathepsin G, interleukin-1β and neutrophil elastase act as objective biomarkers of gingival inflammation induction and resolution that typically precede phenotypical changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
1
17
1
Order By: Relevance
“…The GCF volume reflected GI values, with an evident difference between bleeding sites with moderate inflammation (GI = 2) compared to non‐bleeding sites (GI < 2), and paralleled two objective measures of tissue inflammation, i.e., the percentage of inflamed connective tissue area and the inflammatory infiltrate density . Experimental gingivitis studies demonstrated a clear association between GCF volume and other clinical parameters of gingival inflammation, as well as the concentration of pro‐inflammatory biomarkers . Overall, these and other studies clearly indicate that GCF volume represents a reliable quantitative method to assess the severity of site‐specific, plaque‐induced gingival inflammation in the research setting.…”
Section: Methodssupporting
confidence: 53%
See 2 more Smart Citations
“…The GCF volume reflected GI values, with an evident difference between bleeding sites with moderate inflammation (GI = 2) compared to non‐bleeding sites (GI < 2), and paralleled two objective measures of tissue inflammation, i.e., the percentage of inflamed connective tissue area and the inflammatory infiltrate density . Experimental gingivitis studies demonstrated a clear association between GCF volume and other clinical parameters of gingival inflammation, as well as the concentration of pro‐inflammatory biomarkers . Overall, these and other studies clearly indicate that GCF volume represents a reliable quantitative method to assess the severity of site‐specific, plaque‐induced gingival inflammation in the research setting.…”
Section: Methodssupporting
confidence: 53%
“…Previous studies demonstrated that the quantification of GCF volume is a reliable and accurate indicator of gingival inflammation . In 60 gingival samples retrieved from buccal sites, GCF volume increased with increasing site‐specific GI.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…in 2012 (16) carried out a case-control study in which they also analyzed IL-1β in patients with experimental gingivitis and found that this interleukin increased during experimental gingivitis and then returned to initial levels following the return to normal hygiene. Again in 2012 Becerik et al .…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies have investigated this interleukin, all of them being case-control studies and all analyzing IL-1b in crevicular fluid using the ELISA technique. Some of these studies (9,13,14,16) analyze this interleukin in experimental gingivitis and all found that it is higher in the crevicular fluid of patients with experimental gingivitis and that the levels of this interleukin return to normality following the clinical resolution of the gingivitis (13,16). Three of the studies analyzed this interleukin (5,7,10) in non-experimental gingivitis, the authors finding that IL-1b was higher in patients with gingivitis when compared to those of the control group and that these results were statistically significant.…”
Section: Discussionmentioning
confidence: 99%